2016
DOI: 10.4103/0972-4052.167931
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of effect on water sorption and solubility of a temporary soft denture liner material when stored either in distilled water, 5.25% sodium hypochlorite or artificial saliva: An in vitro study

Abstract: Introduction:Soft denture liners have a key role in modern removable prosthodontics since they restore health to inflamed and abused mucosa by redistribution of forces transmitted to the edentulous ridges. The most common problems encountered using soft denture liners are water sorption and solubility when in contact with saliva or storage media. These problems are associated with swelling, distortion, support of Candida albicans growth, and stresses at the liner/denture base interface that reduces the bond st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Similar finding of increased solubility of soft-liner in artificial saliva was reported by Garg et al6 …”
supporting
confidence: 89%
See 4 more Smart Citations
“…Similar finding of increased solubility of soft-liner in artificial saliva was reported by Garg et al6 …”
supporting
confidence: 89%
“…Leaching of plasticizer causes loss of mass and an increase in solubility. 6 The result of this comparative evaluation on solubility showed that on day 4 mean solubility of soft denture lining material across groups was statistically different (p <0.001). On pairwise comparison, it was found that mean solubility of samples immersed in tea with milk and green tea was significantly higher than that of groups A to C. similarly mean solubility was different at day 7 as well.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations